‘Communicating Manuscripts’: Third Conference of LIBER's Manuscript Librarians Group, Berlin, 28-30 November 2007 - Weber, Jutta; Bouwman, André (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
LIBER's Manuscript Librarians Group held its third conference, entitled 'Communicating Manuscripts' in Berlin from 28-30 November 2007. More than 70 participants from all over Europe came to discuss their experiences and opinions concerning manuscripts (ranging from medieval codices to modern papers and letter collections) — in response to a series of papers delivered by a number of specialists from European research libraries and archival institutions. For the Staatsbibliothek it was a pleasure to welcome them and to make the days in Berlin comfortable and successful.